Krótkie belki na podłożu typu półprzestrzeni sprężystej - MĄCZKA, Janusz; SZEFER, Gwidon (Engineering Transactions, 1970)
Short beams on a base of the elastic half-space typeHere considered is the problem of beams of finite length and variable cross-section -with an arbitrary load and arbitrary boundary conditions -lying upon an elastic base of the elastic halfspace type, consideration being given to the influence of transverse forces. Using the Laplace integral transformation and elements of the theory of distribution, the general solution of the problem is given. For a constant cross-section it was possible to obtain an exact solution in the form of a series of iterated nuclei (with evaluation of the convergence); for the variable cross-section the convergent process of iteration is given. The results are illustrated with a numerical example, which proves that the influence of the transverse forces can be significant.